Correlation between hemoglobin-to-albumin ratio and complications after radical gastrectomy in gastric cancer patients - Luo, Wenbin; Li, Ruoyun; Pan, Chaofan; Luo, Changjiang (Frontiers in Medicine, 2025)
BackgroundPatients who undergo radical gastrectomy for gastric cancer often experience multiple complications that affect the recovery process and reduce quality of life. The hemoglobin-to-albumin ratio (HAR) reflects nutritional status and is widely used to assess various diseases. However, its association with complications after radical gastrectomy in gastric cancer patients has not been fully explored.MethodsThis study retrospectively analyzed clinical and pathological data from 352 gastric cancer patients who underwent radical gastrectomy at the Second Hospital of Lanzhou University between January 2023 and December 2024. The severity of postoperative complications was graded using the Clavien-Dindo classification system, resulting in two groups: non-complication group (n = 254) and Clavien-Dindo ≥II group (n = 98). Multivariate logistic regression models were employed to assess the correlation between HAR and Clavien-Dindo ≥II grade complications. Subsequently, sensitivity analysis, subgroup analysis, restricted cubic spline (RCS) modeling, and threshold effect evaluation were conducted.ResultsMultivariate logistic regression analysis showed that for every 1-unit increase in HAR, the risk of Clavien-Dindo ≥II grade complications decreased by 62.0% (95% CI: 0.188–0.749; p < 0.05). Sensitivity analysis confirmed this conclusion, demonstrating that patients with higher HAR levels exhibited a 64.4% lower risk of complications compared to patients with lower HAR levels (95% CI: 0.170–0.726; p < 0.05). Restricted cubic spline (RCS) analysis demonstrated a negative correlation between HAR and complications, and the threshold effect analysis determined the critical point of HAR to be 2.87. Subgroup analysis showed that most subgroups did not exhibit significant differences in interaction p values. Interestingly, a significant interaction was observed between HAR and platelet (interaction p = 0.011).ConclusionThis study indicates that higher HAR is significantly and negatively correlated with the risk of complications. Higher levels of HAR effectively prevent Clavien-Dindo ≥ II-grade complications. Consequently, HAR can serve as a clinically useful indicator for predicting complications following radical gastrectomy for gastric cancer.